COVID-19 and Diabetes: Persistent Cardiovascular and Renal Risks in the Post-Pandemic Landscape - Tzu-Shan Huang; Jo-Yen Chao; Ho-Hsiang Chang; Wei-Ren Lin; Wei-Hung Lin (Life)
The Coronavirus Disease 2019 (COVID-19) pandemic, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), disproportionately affects individuals with diabetes mellitus (DM) by exacerbating cardiovascular and renal complications. This increased risk is mediated through immune dysfunction, chronic inflammation, hyperglycemia, dysregulation of renin-angiotensin system dysregulation, endothelial dysfunction, and hypercoagulability. Epidemiological studies indicate a two-fold increased risk of stroke and end-stage renal disease in SARS-CoV-2-infected individuals with diabetes, along with a 60% higher risk of cardiovascular disease. While antidiabetic therapies like sodium-glucose cotransporter-2 inhibitors and glucagon-like peptide-1 receptor agonists show potential protective effects, insulin use in hospitalized patients is linked to higher mortality. Vaccination is crucial in reducing severe COVID-19 outcomes and mitigating post-infection complications, including new-onset diabetes. While concerns exist regarding vaccine-associated nephropathy and thromboembolic events, these risks are thought to be minimal compared to the benefits. As COVID-19 shifts to an endemic phase, the long-term renal and cardiovascular outcomes in patients with DM remain uncertain, highlighting the urgent need for continued research and targeted management strategies.